Agrobiodiversity Conservation: Securing the Diversity of Crop Wild Relatives and Landraces - Maxted, Nigel (CABI, 2014)
Genetic variation used in variety breeding originates to a large extent from the ancestral species of the crops and is being managed by breeders in breeding pools. Genetic bottle- necks caused right at the beginning of the domestication process or caused by breeding at a later stage of the domestication process (e.g. Kilian et al., 2006) necessitates the intro- gression of novel genetic variation from the crop's gene pool into the breeding pools. Crop wild relatives (CWR) and landraces (LR) are part of this gene pool, which is tapped by breeders if need arises. Without this flow of novel genes from wild species and landraces into the breeding pools the adaptability of crops to changing environ- mental conditions and user demands would be very difficult to maintain today and in the future. The demand for traits and trait varia- tion can be forecasted by plant breeders for the next 10-20 years while a prognosis of the future needs of agriculture is not possible beyond this time horizon.